The Effect Of Differences In Reinforcement Type In Educational Blogs On Cognitive Achievement In Computer Subject To The Third-Grade Students Intermediate - Ali, Akram Fathi Mostafa; Al Selmi, Fawaz (Journal of Humanities & Social Sciences, 2018)
This study aimed to statement the effects of the differences in reinforcement (Verbal written with a picture/ verbal written with illustrations) type in educational blogs learning for third- grade in Intermediate education through the answer Of the following question: What is the effect of differences in reinforcement (Verbal written with a picture/ verbal written with illustrations) type in educational blogs on cognitive achievement in computer subject to the third-grade students Intermediate ? To answer this question، two blogs of educational learning different in the type of reinforcement were designed. The first is: Verbal written with a picture/. The second is: verbal written with illustrations. The sample was (60) students selected from Intermediate Attaban bin Malik in Jeddah province in Makah region. The results of the study revealed: There is no statistically significant differences between the mean scores of the two experimental groups students in the post application to test the cognitive achievement attributed to the type of in reinforcement (Verbal written with a picture/ verbal written with illustrations.
Keywords: reinforcement; educational blogs; form of reinforcement; cognitive achievement